What do you Know about ODE?

Calculus Level 4

d y d x = 2 e 2 x sin ( y ) + x y 2 e 2 x cos ( y ) + x 2 y \frac{dy}{dx}=-\dfrac{2e^{2x}\sin(y)+xy^2}{e^{2x}\cos(y)+x^2y} Given the ODE above and knowing the point ( 0 , π 2 ) (0,\frac{\pi}{2}) belongs to its solution. If the point ( a π , π ) (\frac{\sqrt{a}}{\pi},\pi) belongs to the solution too, find the value of a a .


The answer is 2.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

An exact ODE has the form: A ( x , y ) d y + B ( x , y ) d x = 0 A(x,y)dy+B(x,y)dx=0 Where there is a C 2 C^{2} function F ( x , y ) F(x,y) such that F y = A ( x , y ) \frac{\partial F}{\partial y}=A(x,y) and F x = B ( x , y ) \frac{\partial F}{\partial x}=B(x,y) , which means that 2 F x y = A x = B y \frac{\partial ^{2} F}{\partial x \partial y} = \frac{\partial A}{\partial x} = \frac{\partial B}{\partial y} . Being F ( x , y ) = 0 F(x,y)=0 the solution to the ODE as an implicit function. Using this, the ODE above can be written as: ( e 2 x cos ( y ) + x 2 y ) d y + ( 2 e 2 x sin ( y ) + x y 2 ) d x = 0 (e^{2x}\cos(y)+x^2y)dy+(2e^{2x}\sin(y)+xy^2)dx=0 And also we have x ( e 2 x cos ( y ) + x 2 y ) = 2 e 2 x cos ( y ) + 2 x y = y ( 2 e 2 x sin ( y ) + x y 2 ) \frac{\partial}{\partial x}(e^{2x}\cos(y)+x^2y)=2e^{2x}\cos(y)+2xy=\frac{\partial}{\partial y}(2e^{2x}\sin(y)+xy^2) So the ODE is said to be exact. F ( x , y ) y = e 2 x cos ( y ) + x 2 y F ( x , y ) x = 2 e 2 x sin ( y ) + x y 2 \Rightarrow \frac{\partial F(x,y)}{\partial y}=e^{2x}\cos(y)+x^2y \wedge \frac{\partial F(x,y)}{\partial x} =2e^{2x}\sin(y)+xy^2 With the first equation: F ( x , y ) = e 2 x sin ( y ) + x 2 y 2 2 + C ( x ) F(x,y)=e^{2x}\sin(y)+\frac{x^2y^2}{2}+C(x) Where C ( x ) C(x) is an arbitrary function of y y . \ Replacing in the second equation: 2 e 2 x sin ( y ) + x y 2 + C ( x ) = 2 e 2 x + x y 2 C ( x ) = 0 C ( x ) = k 2e^{2x}\sin(y)+xy^2+C'(x)=2e^{2x}+xy^2 \Rightarrow C'(x)=0 \Rightarrow C(x)=k F ( x , y ) = e 2 x sin ( y ) + x 2 y 2 2 + k \Rightarrow F(x,y)=e^{2x}\sin(y)+\frac{x^2y^2}{2}+k So the solution of the ODE can be expressed as: e 2 x sin ( y ) + x 2 y 2 2 + k = 0 e^{2x}\sin(y)+\frac{x^2y^2}{2}+k=0 And replacing the point ( 0 , π 2 ) (0,\frac{\pi}{2}) which belongs to the solution: e 2 x sin ( y ) + x 2 y 2 2 = 1 e^{2x}\sin(y)+\frac{x^2y^2}{2}=1 So, replacing in the asked point ( x , π ) (x,\pi) : e 2 x 0 + x 2 π 2 2 = 1 x = 2 π e^{2x}\cdot 0+\frac{x^2\pi^2}{2}=1 \Rightarrow x=\frac{\sqrt{2}}{\pi}

I thought ODE stands for Ordinary Differential Equations as this was an easy one for any jee aspirant.

Archit Tripathi - 4 years, 5 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...